2016
DOI: 10.1681/asn.2015050568
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Regulates Extracellular Vesicle Uptake by Kidney Collecting Duct Cells

Abstract: Extracellular vesicles (ECVs) facilitate intercellular communication along the nephron, with the potential to change the function of the recipient cell. However, it is not known whether this is a regulated process analogous to other signaling systems. We investigated the potential hormonal regulation of ECV transfer and report that desmopressin, a vasopressin analogue, stimulated the uptake of fluorescently loaded ECVs into a kidney collecting duct cell line (mCCD) and into primary cells. Exposure of mCCD cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
(43 reference statements)
1
50
1
Order By: Relevance
“…( Figure 3A). Haemodialysis induced a statistically significant, but clinically insignificant, increase in ALT from 12 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) to 13 (11-21) IU l À1 . By contrast with ALT, miR-122 was not different when healthy controls were compared with CKD ( Figure 3B).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…( Figure 3A). Haemodialysis induced a statistically significant, but clinically insignificant, increase in ALT from 12 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) to 13 (11-21) IU l À1 . By contrast with ALT, miR-122 was not different when healthy controls were compared with CKD ( Figure 3B).…”
Section: Resultsmentioning
confidence: 90%
“…The Ago2-bound form of miR-122 may be more sensitive to enzymatic digestion compared with ECV-encapsulated miR-122. A priori it could be hypothesized that the ECV fraction would differ between patients with ESRD and healthy controls because work by our group [17], and others [18], has clearly demonstrated that systemically injected ECVs are excreted in urine. This would suggest that their clearance may be altered in ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that transport of EVs into cells is a specific and tightly regulated process. For example, the transport of renal tubular EVs carrying miR-503 into collecting duct epithelial cells has been shown to be hormonally regulated (118).…”
Section: Effect Of Mirs Within Evs On Apoptosismentioning
confidence: 99%
“…This process can be manipulated to deliver miRNA to collecting duct cells resulting in downregulation of target transcripts (Oosthuyzen et al . ). This study demonstrated that uEV signalling is a physiologically regulated process, which can be manipulated to deliver miRNA.…”
Section: Introductionmentioning
confidence: 97%